The comprehensive autism planning system (CAPS) for individuals with autism spectrum disorders and related disabilities : integrating evidence-based practices throughout the student's day - Henry, Shawn; Myles, Brenda Smith (Kansas : AAPC Publishing, 2013)
This system allows educators to understand how to implement an instructional programme for students with ASD. Known as CAPS, the model answers common questions about finding the right supports to fit a child$1 (Bs learning style in order to help him reach his full potential. Used with The Ziggurat Model, CAPS enables educators and other professionals to address adequate yearly progress (AYP), response to intervention (RTI), and positive behaviour support (PBS). This expanded second edition of CAPS adds important new material on technical assistance/consultation as well as up-to-date considerations of current mandates and trends that support CAPS use, including a major focus on evidence-based practices.s
Includes index and glossary.
Keywords: Autism spectrum disorders -- -- Patients -- Education; Autistic children -- Education; Autistic youth -- Education